Interaction of Islam with Local Culture - Zayadi Hamzah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
To understand the social and religious phenomena associated with Islamic relations with local culture in the rite of the passage of the family in general with respect to the scope of religious theory as a cultural or religious subsystem as social reality, where religion (Islam) is a social reality confronted with the process of interaction of Islam with the local culture in which Islam is embraced.The process of interaction of Islam with local culture in this study is expected to give birth to acculturation, assimilation, accommodation, conflict, and integration. This process looks at how acculturation, assimilation, accommodation, conflict, and integration exist between Islam and local culture in a social constructivist framework by focusing on what lies behind actions, from the various rituals of the family life cycle. It is assumed that Islamic relations with local culture will occur in several forms: first: the possibility of coexistence or adhesion between Islam and Rejang culture without mutual intervention and interruption; second: the possibility of integration or cohesion whether in the form of Islamic permeation into local culture or adaptation of local culture to Islam, both symbolically and substantially, and third: the possibility of conflict between Islam and local culture both latent and manifest